Pelatihan pembuatan media interractive quiz menggunakan power point dan quiziz - Elfi Rahmadhani (Rengganis Jurnal Pengabdian Masyarakat, 2022)
Teachers are the main key in efforts to improve the quality of education. Improving and developing the professionalism of teachers in the 21st century, it can be done with ICT-based learning. One alternative is to make interactive quiz media using PowerPoint and quiziz. Making this media was chosen because some teachers have never evaluated learning using technology. Especially during the current pandemic conditions, teachers are expected to be more creative in providing subject matter and keep students enthusiastic about learning from home. With the implementation of this training, it is expected that teachers can master and utilize the PowerPoint media and quiziz application in providing learning evaluations. Based on the training that has been given, it is known that the participants are very interested and feel helped by this interactive quiz media creation training. It can be seen from the results of the evaluation of the questionnaire given at the last meeting, that 85% of the participants were very satisfied with the training provided.